Reduced Gene Expression of Peroxisome Proliferator-Activated Receptor Gamma Coactivator-1α in Whole Blood in Euthyroid Patients One Year After Hemithyroidectomy for Benign Euthyroid Goiter - Kristensen, Tina Toft; Pedersen, Palle Lyngsie; Larsen, Jacob; Feldthusen, Anne-Dorthe; Jelstrup, Søren; Ellervik, Christina (Hormone and Metabolic Research, 2019)
We have previously reported decreased thyroid function within the laboratory reference range and changes in mitochondrial function after hemithyroidectomy. Peroxisome proliferator-activated receptor γ coactivator-1α (PGC-1α) and coactivator-1β (PGC-1β) are key regulators of mitochondrial biogenesis and function. The aim was to examine the influence of hemithyroidectomy on the longitudinal change in mRNA expression of these genes. In addition, we measured longitudinal changes in mRNA expressions of the mitochoncrial-related genes nuclear factor erythroid-derived 2-like 2 (NFE2L2), mitochondrial transcription factor A (TFAM), and sodium dismutase 2 (SOD2). Twenty-eight patients were examined before and 1, 3, 6, and 12 months after hemithyroidectomy for benign euthyroid goiter. Thyroid stimulating hormone (TSH) and thyroid hormones were measured, and whole blood gene expression of PGC-1α, PGC-1β, NFE2L2, TFAM, and SOD2 was examined by reverse transcription quantitative Polymerase Chain Reaction. We used mixed effect regression models to investigate changes in gene expression with time. Averaged over all follow-up visits, TSH increased (p=0.001), tT3 declined (p=0.01), and fT4/tT3 ratio increased (p=0.03) over one-year follow-up, but fT4 remained unchanged. Averaged over all follow-up visits, whole blood PGC-1α levels (p<0.001) and SOD2 (p=0.009) levels declined, but PGC-1β, TFAM, and NFE2L2 did not change over one-year follow-up. The study demonstrates significant downregulation of whole blood PGC-1α and SOD2 gene expressions in hemithyroidectomized patients with a concomitant increase in TSH concentration within the reference range. Thus, hemithyroidectomized patients may likely have impaired mitochondrial function.
Keywords: thyroidectomy; thyroid hormone; hypothyroidism; peroxisome proliferator-activated receptor gamma coactivator-1α; sodium dismutase 2